Provenance of the Mesozoic Succession of Franz Josef Land (North‐Eastern Barents Sea): Paleogeographic and Tectonic Implications for the High Arctic. Issue 11 (19th November 2022) - Ershova, Victoria; Prokopiev, Andrei; Stockli, Daniel; Kurapov, Mikhail; Kosteva, Natalia; Rogov, Mikhail; Khudoley, Andrei; Petrov, Eugeny O.
Abstract: Study of the Mesozoic succession of Franz Josef Land (FJL) has shed new insights on the stratigraphy and geological history of the neighboring portion of the Arctic. Based on the composition of pebbles and cobbles from Lower Jurassic conglomerates, we suggest that the pre‐Mesozoic stratigraphy of the NE Barents Sea comprises Cambrian metasandstones intruded by Late Paleozoic granites and overlain by Carboniferous–Permian sedimentary deposits. U‐Pb and ZHe ages of detrital zircons from Uppermost Triassic–Lower Cretaceous strata of FJL reveal Precambrian to Early Mesozoic grains. The most abundant Late Paleozoic detrital zircon population suggests the existence of the same in age magmatic events in the provenance area. ZHe ages show Late Triassic (ca. 225 Ma) exhumation of the provenance area. Moreover, the youngest grains of detrital zircons are Middle‐Late Triassic in age pointing that significant uplift of provenance coincides with magmatic activity. Based on these data, we suggest that the provenance area for Triassic–Lower Cretaceous strata of FJL was characterized by a similar geological composition, as well as magmatic and tectonic history, to the Taimyr fold‐and‐thrust belt and Kara terrane. A comparison of detrital zircon data from coeval strata elsewhere in the Arctic realm suggests that this eastern provenance area was actively sourcing sediments right across the Barents Sea Basin, and possibly as far as the Sverdrup basin, during the Latest Triassic–Jurassic. The period of Late Triassic uplift represented a significant tectonic event across the north‐eastern Barents Sea, and likely initiated an increase in sediment supply and a reorganization of pre‐existing sediment transport pathways. Key Points: Pre‐Mesozoic rocks of NE Barents Sea are Cambrian metasediments intruded by Late Paleozoic granites and overlain by Upper Paleozoic deposits Triassic–Lower Cretaceous strata of Franz Josef Land were sourced from a proximal provenance area uplifted in the Late Triassic Two major shifts in sedimentary transport pathway occurred in Barents Sea and Sverdrup basins in Late Triassic and Late Jurassic